Macrozoobenthos structure in a temperate acid oligotrophic lake - Mimier, Daria; Godzich, Magdalena; Żbikowski, Janusz (Ecological Questions, 2017)
The aim of the paper was to evaluate the structure of macrozoobenthos in acid, oligotrophic Jasne Lake. The basic abiotic parameters of water and bottom sediments were also studied. The samples were taken on five dates: 25.11.1997 and 13.05., 01.07., 7.08. and 21.10. in 1998. The sampling sites were located in four clearly different zones of the lake bottom at depths: 5 m, 10 m, 15 m and 19 m. The water transparency was very high (11 m) and water pH was extremely low (4.3). The oxygenation of the water near bottom was quite good up to a depth of 10 m. Generally both the water content (75.9% – 96.1%) and organic matter content (17.5% – 76.5%) in the bottom sediments were relatively high and increased with the depth. The taxonomic composition of the macrozoobenthos was similar to that of other acid water bodies, i.e. common, ubiquitous taxa dominated. Its species richness, diversity, and the density decreased as the depth increased but it is worth noting that the zone colonized by diverse and abundant macrozoobenthos extends to a depth of at least 10 m. The dominant group of benthic fauna at a depth of 5 m were Chironomidae larvae (almost 80% of the total macrozoobenthos density). At this station Ceratopogonidae and Sialis sp. larvae were also relatively numerous. In turn, at depths of 10 m and 15 m Asellus aquaticus (Isopoda) (43% and 57%, respectively) and Trichoptera larvae (37% and 21%, respectively) dominated. Among the chironomids Pseudochironomus sp. and Chironomus sp. larvae prevailed. The only taxa characteristic of acidic waters were Stylodrilus heringianus (Oligochaeta) and Ablabesmyia monilis (Chironomidae).